Forecasting speed-strength abilities in young chinese volleyball players - Peng, Zhao (Theory and Practice of Physical Culture, 2026)
Objective of the study is to examine and substantiate a system for predicting speed-strength abilities of young Chinese volleyball players. Results and conclusions. Predicting physical qualities and abilities in volleyball during the process of selecting children should be carried out using indicators of a two-legged standing vertical jump and a seated medicine ball throw (1 kg). The preparation of a sports reserve in volleyball is associated with a system of effective prediction of physical qualities and abilities that determine the patterns of forming rational motor actions. The development of criteria for predicting the most important aspects of volleyball players’ preparedness subsequently determines the success of athletes’ participation in the training and competitive processes.